Gone with the wind? Electricity market prices and incentives to invest in thermal power plants under increasing wind energy supply - Thure Traber; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The increased wind energy supplied to many electricity markets around the world has to be balanced by reliable back up units or other complementary measures when wind conditions are low. At the same time wind energy impacts both, the utilization of thermal power plants and the market prices. While the market prices tend to decrease, the impact on the utilization of different plant types is at the outset unclear. To analyze the incentives to invest in thermal power plants under increased wind energy supply, we develop a computational model which includes start-up restrictions and costs and apply it to the German case. We find that due to current wind supply the market prices are reduced by more than five percent, and the incentives to invest in natural gas fired units are largely decreased. An increased wind supply erodes their attractiveness further. Consequently, a gap between the need for and the incentive to provide exibility can be expected.
Keywords: C63; L13; L94; Q42; 330; Electricity market modeling; start-up costs; wind energy; oligopoly; Stromtarif; Elektrizitätswirtschaft; Oligopol; Windenergie; Wärmeenergie; Gaswirtschaft; Investition; Ökonomischer Anreiz; Deutschland